Німецькі новорічні та різдвяні поштівки епохи модерну із колекції Полтавського краєзнавчого музею імені Василя Кричевського - Сулима, О.С. (Сіверщина в історії України, 2021)
У статті охарактеризована колекція художніх поштових карток кін. ХІХ – поч. ХХ ст. з привітаннями до Різдва та Нового
року (описані етапи формування збірки, встановлені видавці та
уточнене датування). Дослідження зосереджене на поштівках німецьких типографій – лідерів серед зарубіжних видавництв, що
випускали продукцію для ринку Російської імперії. Особлива увага приділена семіотичному аналізу символів та образів, що використані ілюстраторами для створення святкового настрою поштових карток. Вітальні поштові листівки містять закодовані
послання, звичні для людей модернової доби, однак на сучасному історичному етапі вони втратили первісні ознаки та потребують
додаткових роз’яснень. Наведений анотований список німецьких
різдвяних та новорічних поштівок кін. ХІХ – поч. ХХ ст. із зібрання Полтавського краєзнавчого музею імені Василя Кричевського. Postcards of the late 19th – early 20th cc. are valuable written
and iconographic data medium. They are important part of unique
encyclopedia of social life of the Modernist Time. The article contains
characteristic of pictorial postcards collection of the mentioned period
with Christmas and New Year greetings. Using historic source research
instruments, method of inner and outer source critic in particular,
attribution of research objects was made, including stages of gathering
forming description, finding publishers and dating each of chosen museum
objects. The research is concentrated at postcards of German publish
houses – leaders among foreign publishers, that released production
in Russian Empire. There are 18 units of German production among 34
objects of subgroup “New Year and Christmas postcards of the late 19th
– early 20th cc.” in the Vasyl Krychevsky Poltava Local Lore Museum
deltilogical collection.
Special attention is paid to semiotic analysis of symbols and
characters, and also most widespread cultural structures, that were
used by illustrators for creating holiday mood of postcards. Greeting
postcards contain hidden messages, ordinary for people of the Modernist
Time, though they lost their meaning at the current historic stage and
need special explanations. In particular, such popular New Year and
Christmas symbols as Father Christmas, winter landscapes, religious
buildings, archways, bells, stars, calendars, floral and zoomorphic motives,
fairytale characters – dwarves, angels etc. are decoded. Tradition of New
Year cultural structure – elm-tree – is observe separately.
Results of investigation are concentrated in annotated list of German
Christmas and New Year postcards of the late 19th – early 20th cc. in the
Vasyl Krychevsky Poltava Local Lore Museum gathering.